Self-medication pattern among medical students in Middle Delta, Egypt - Nadira Mansour Hassan; Shimaa Mohamed Mohamed Koabar (BMC Medical Education)
Abstract Background Self- medication leading to wastage of limited resources in developing countries, prolonged suffering, increase resistance to drugs and may result in significant medical complications such as adverse drug responses and dependence. Self-medication is extensively used by health professionals. Undergraduate medical students as being the future physicians representing a main pillar in health care system thus have special significance. This study aimed to estimate the prevalence of self-medication and identify its pattern among medical students in Tanta university, Egypt. Methods A four-month cross-sectional study was carried out among Egyptian undergraduate medical students at Tanta University, from first to final year. (November 2023 – February 2024). The students were chosen using a two-stage cluster sampling method, and data on sociodemographic and self-medication patterns were collected using a predesigned semi-structured self-administered questionnaire. Results The prevalence of self-medication was 71%. The key determinants of self-medication was students’ medical knowledge from self- experience and studies (55.9%). Headache was a common complaint for self-medication (80.4%). Majority of them (88.3%) use pharmaceutical products where analgesics lies on top (92.4%). The degree of popularity of the medicine was the primary reason for drug selection (52.5%) and recommendation of the pharmacist was the main determinate of selecting type of drug (43.6%). However, 30.2% experienced side effects, of which 50% went to private physician and 33.5% stopped taking their medications. Half of the students took antibiotics for self-medication. Conclusions Self-medication is a common practice among medical students. where headache was the common symptom and the most commonly utilized medications for self-medication were analgesics. There is a need to augment the value of diagnosis, awareness and seriousness of this practice.